Evolution and Characteristics of Territorial Economic Disparities in Romania - Benedek, József; Kurkó, Ibolya (Theory, Methodology, Practice – Review of Business and Management, 2011)
The territorial disparities of Romania, as well as of other states, are a fundamental characteristic of the society’s spatiality, with the changes thereof being conditional upon multiple factors. The economy and the society are unequally distributed spatially, this phenomenon being also accentuated by the regional and local specificities and by the different spatial way of manifestation of the natural, cultural economic and social factors. The unequal spatial distribution of the economic activities, transport infrastructures, settlements and population imprints paths of territorial development, sometimes strongly differentiated locally and regionally. Further on, we shall focus on the analysis of the territorial disparities in Romania, from geographic and economic perspectives.